2020
DOI: 10.1186/s12936-020-03412-4
|View full text |Cite
|
Sign up to set email alerts
|

Individual, community and region level predictors of insecticide-treated net use among women in Uganda: a multilevel analysis

Abstract: Background Use of insecticide-treated net (ITN) has been identified by the World Health Organization as an effective approach for malaria prevention. The government of Uganda has instituted measures to enhance ITN supply over the past decade, however, the country ranks third towards the global malaria burden. As a result, this study investigated how individual, community and region level factors affect ITN use among women of reproductive age in Uganda. Methods The 2018–2019 Malaria Indicator Survey of Uganda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
3
7
0
Order By: Relevance
“…The study found that 58.37% of pregnant women slept under a net. This result is consistent with previous studies [ 28 , 29 , 30 , 31 , 32 ]. Women’s educational level was associated with ITNs usage among pregnant women; those with secondary or higher educational levels were more likely to sleep under a net than those who had no education.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The study found that 58.37% of pregnant women slept under a net. This result is consistent with previous studies [ 28 , 29 , 30 , 31 , 32 ]. Women’s educational level was associated with ITNs usage among pregnant women; those with secondary or higher educational levels were more likely to sleep under a net than those who had no education.…”
Section: Discussionsupporting
confidence: 94%
“…This finding is similar to that of other studies in Ghana and Cameroon [ 41 , 42 ]. In contrast, Ameyaw et al [ 31 ] noted that rural residents in Uganda have a lower chance of using ITNs than urban residents following a national mass-distribution exercise.…”
Section: Discussionmentioning
confidence: 97%
“…The odds of ITNs utilization was two times higher among urban resident pregnant women compared to the rural residents. This is consonant with the studies conducted in sub-Saharan Africa, 25 Tigray, 14 Northwest Ethiopia, 24 and Adama. 9 The reasons might be urban residents were near mass media, and health facilities/health professionals to get information and awareness regarding malaria prevention methods using ITNs, and they are near the market to buy ITNs.…”
Section: Discussionsupporting
confidence: 86%
“…Similarly, the odds of ITNs utilization was two times higher among pregnant women with monthly income >1050 Ethiopian total birr compared to their counterparts. This is supported by the findings of the studies conducted from sub-Saharan Africa 25 and North western Ethiopia 28 where pregnant women with income ≥151 dollar were more likely to utilize ITNs. This might be due to pregnant women with high income being able to access health services and having the ability to buy ITNs.…”
Section: Discussionsupporting
confidence: 54%
“…Many studies concluded that the individual’s economic status was associated with levels of malaria preventive practice in the community [ 10 , 26 28 ]. Mostly, ITNs are distributed free of charge directly to the hands of pregnant women.…”
Section: Discussionmentioning
confidence: 99%